Pengaruh Tingkat Pendapatan, Sanksi Pajak, Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi: (Studi Kasus Pada PT X) - Fathurrahman, Isyrin; samanto, Hadi; Pravasanti, Yuwita Ariessa (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
This study examines the influence of income level, tax sanctions, and taxpayer awareness on individual taxpayer compliance. The research was conducted using a quantitative approach with a survey method, involving 100 respondents who are permanent employees of PT X. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that income level has no significant effect on tax compliance, suggesting that the amount of income is not a reliable predictor of compliance behavior. Tax sanctions, however, have a positive and significant effect, demonstrating that stricter enforcement of tax penalties can effectively improve compliance. Meanwhile, taxpayer awareness does not show a significant influence, implying that knowledge and positive attitudes toward taxation have not yet translated into consistent compliant behavior. Overall, the model explains 68.5% of the variation in compliance, with the remaining 31.5% influenced by other factors not included in this study. The findings highlight the importance of consistent and fair enforcement of tax sanctions, while also pointing to the need for further efforts to strengthen taxpayer education and trust in the tax system.